Futures consciousness and its impacts on the individual’s readiness to make radical policy choices – study on Finnish regime members - Sanna Ahvenharju (Belgium, 2022)
Future consciousness is typically considered an essential feature of good policy-making and a prerequisite for radical innovations and game-changing shifts in policy. The styles of future thinking have, however, rarely been studied among regime members. This paper utilises a new method to measure future consciousness and evaluates its relationship with acceptance and interest in new, radical policy shifts among individual regime members. The purpose of this paper is to find correlations between the different futures consciousness profiles and the attitudes towards new types of policies and policy shifts among regime representatives by cross-analysing three different types of data.
The data includes futures consciousness profiles and opinions of 21 Finnish regime representatives: policy makers, executives from government ministries, city majors, heads of trade unions and other interest groups and businesses. The regime representatives participated in a three part study: 1 – futures consciousness psychometric test; 2 – individual interviews on their future visions and challenges related to natural resource scarcity; and 3 – survey on the acceptability of new strong consumption household consumption policies. The participants were asked to participate as individuals and express their personal opinions. The strong consumption policies evaluated in the survey were developed based on expert interviews and a literature review. These fourteen policy measures varied from resource tax to urban planning codes and from personal consumption footprints to wage caps.
The futures consciousness psychometric test is a new, recently developed instrument for measuring the presence and impacts of future consciousness in individuals. It builds on a novel five-dimensional model of futures consciousness, which integrates theoretical thinking from futures studies with relevant psychological literature and constructs. It consists of the following psychological dimensions a) Time Perspective, b) Agency Beliefs, c) Openness to Alternatives, d) Systems Perception, and e) Concern for Others.
According to the analysis, the regime representatives formed three different groups: the radicals, the moderates and the critics. Each one of the groups has varying scores in the futures consciousness scale and their scores can partly explain their policy choices. The moderates score high in systems perception and hence they prefer policies that are in line with current, existing policies. The radicals have strong openness to alternatives and concern for others so they are more inclined towards new policies. The critics score high in openness to alternatives but low in time perspective and they are less likely to accept restrictive policies and more likely to trust that solutions will be found in the future.
The initial results provide insight on the role of futures consciousness in relation to individual’s interest in supporting new policies and radical policy shifts. This, in turn, will increase our understanding on the psychological processes behind decision-making and policy choices. It also gives insight on the question of how new policies should be developed and promoted to gain wide support among different kinds of regime members.
It should be noted that the results presented in this paper are preliminary.
FTA2018 - Future in the making